2013
DOI: 10.1016/j.yexcr.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of mouse TTC30/DYF-1 with multiple intraflagellar transport complex B proteins and KIF17

Abstract: Intraflagellar transport (IFT) is a microtubule based system that supports the assembly and maintenance of cilia. Genetic and biochemical studies have identified two distinct complexes containing multiple proteins that are part of the IFT machinery. In this study we prepared mouse pituitary cells that expressed an epitope-tagged IFT protein and immuno-purified the IFT B complex from these cells. Mass spectrometry analysis of the isolated complex led to identification of a number of well known components of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Interaction studies of IFT-B core proteins using yeast two-hybrid analysis or bacterial coexpressions/pulldowns suggested direct interactions between IFT27 and IFT25 (Follit et al 2009;Wang et al 2009;Bhogaraju et al 2011), IFT70 andIFT52 (Zhao andMalicki 2011;Howard et al 2013), IFT70 and IFT46 (Fan et al 2010), IFT81 and IFT74 (Lucker et al 2005;Kobayashi et al 2007), IFT88, IFT52, and IFT46 (Lucker et al 2010), and, finally, IFT56 and IFT46 (Swiderski et al 2014). These initial insights into subunit interactions paved the way for the recombinant reconstitution of several IFT-B core subcomplexes using Chlamydomonas proteins ) as well as a nine-subunit IFT-B core lacking only IFT56 (Taschner et al 2014).…”
Section: The Architecture Of the Ift-b Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction studies of IFT-B core proteins using yeast two-hybrid analysis or bacterial coexpressions/pulldowns suggested direct interactions between IFT27 and IFT25 (Follit et al 2009;Wang et al 2009;Bhogaraju et al 2011), IFT70 andIFT52 (Zhao andMalicki 2011;Howard et al 2013), IFT70 and IFT46 (Fan et al 2010), IFT81 and IFT74 (Lucker et al 2005;Kobayashi et al 2007), IFT88, IFT52, and IFT46 (Lucker et al 2010), and, finally, IFT56 and IFT46 (Swiderski et al 2014). These initial insights into subunit interactions paved the way for the recombinant reconstitution of several IFT-B core subcomplexes using Chlamydomonas proteins ) as well as a nine-subunit IFT-B core lacking only IFT56 (Taschner et al 2014).…”
Section: The Architecture Of the Ift-b Complexmentioning
confidence: 99%
“…Regarding direct attachment points between motors and cargos, it was found that Dyf-1 in C. elegans (the worm homolog of the IFT-B1 protein IFT70) is necessary for binding and/or activation of the OSM-3 motor, because in dyf-1 mutants the IFT trains are moved only by heterotrimeric kinesin II, and the OSM-3 dependent distal singlet segment fails to form (Ou et al 2005a). A direct interaction between the homologous proteins in mammals was suggested (Howard et al 2013).…”
Section: Association Between Ift Complexes and Ift Motorsmentioning
confidence: 99%
“…In C. elegans amphid channel cilia, heterotrimeric kinesin‐2 (aka kinesin‐II) appears to bind and transport IFT‐A, whereas homodimeric kinesin‐2 (OSM‐3) binds IFT‐B, because in BBSome mutants, the kinesin‐II/IFT‐A and OSM‐3/IFT‐B subcomplexes move separately along the axoneme at 0.5 and 1.2 μm·s −1 respectively . The IFT‐B1 subunit, IFT‐70 (DYF‐1) was proposed to be involved in the IFT‐B/OSM‐3 interaction, which is supported by coimmunoprecipitation experiments in mouse, suggesting that IFT70 binds to multiple IFT‐B subunits and to homodimeric kinesin‐2 (KIF17) . In contrast to the findings from C. elegans however, coimmunoprecipitation experiments in Chlamydomonas (which lacks homodimeric kinesin‐2) and mouse suggest that heterotrimeric kinesin‐2 binds directly to IFT‐B rather than IFT‐A , but the significance of this difference is unclear.…”
Section: Biochemistry and Functions Of Components Of The Ift Machinerymentioning
confidence: 99%
“…The inability of KIF17 to rescue ciliogenesis was surprising as mammalian KIF17 is an active kinesin motor [73] that localizes to mammalian cilia [74], binds to IFT proteins [46, 75], moves in an IFT-like manner in mammalian cilia [45, 76], and influences the ciliary localization of some signaling proteins [39, 77]. We thus considered the possibility that heterotrimeric KIF3A/KIF3B/KAP plays a critical role during cilium assembly, but that KIF17 is able to drive sufficient IFT events for cilium maintenance.…”
Section: Discussionmentioning
confidence: 99%